Characterizing the Type of Outcome Evoked by the Perfect Simple and the Perfect Progessive in English - Bégin, Claude (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1996)
ABSTRACTMany grammarians of English agree that the simple and progressive forms of the Perfect evoke outcomes of different kinds. Thus for example in: I have mowed the lawn the Perfect Simple evokes a completed activity and so points to the present state of the lawn, whereas its progressive counterpart, I have been mowing the lawn, evokes an incomplete activity and so could readily be used as a means of explaining why the subject is perspiring, for example. Obvious though this difference may be, no grammarian has yet been able to characterize these outcomes and explain how each is produced by the verb form. This, then, is the aim of the present paper.